2023
DOI: 10.1093/asjof/ojad018
|View full text |Cite
|
Sign up to set email alerts
|

The Best Under Stress: An Analysis of Breast Tissue Expander Response to External Forces

Abstract: Background The use of breast tissue expanders (TE) in breast reconstruction is accompanied by undesired changes to the chest wall and lateral plane. Breast TEs are designed to create a naturally formed breast pocket by capitalizing on the ductile response of skin tissue; however, in practice, the use of expanders is accompanied by undesired changes to the chest wall and lateral plane. Objectives The authors of this study comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…With the addition of this feature, the Artoura purports to offer more consistent and predictable outcomes of pocket formation 9 . Najafali et al demonstrated that with applied mechanical compression forces, Artoura TEs have the least lateral distortion and forward projection loss when compared with other TE 10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With the addition of this feature, the Artoura purports to offer more consistent and predictable outcomes of pocket formation 9 . Najafali et al demonstrated that with applied mechanical compression forces, Artoura TEs have the least lateral distortion and forward projection loss when compared with other TE 10 …”
mentioning
confidence: 99%
“…9 Najafali et al demonstrated that with applied mechanical compression forces, Artoura TEs have the least lateral distortion and forward projection loss when compared with other TE. 10 Although the literature on breast TEs in general has been well studied, few studies have investigated the complications associated with specific TE subtypes, particularly since the larger adoption of smooth models. It remains unclear what actual differences, if any, exist practically between different models.…”
mentioning
confidence: 99%
“…This experimental study was designed to test the deformational properties of 3 commercially available breast tissue expanders distributed by Mentor (Irvine, CA), Allergan (Irvine, CA), and Sientra (Santa Barbara, CA). 1 The purpose was to determine if various compressive loads, when applied to a fully filled saline tissue expander, would result in deformation based on base width, projection, and height. The implication being that this could affect clinical outcomes.…”
mentioning
confidence: 99%
“…We appreciate the reader's input and thoughtful commentary on our recent article on the deformational forces of 3 commercially available tissue expanders (TEs). 1 , 2 The author raises a valid point that advancements in reconstructive plane utilized, namely prepectoral, alter the intracorporal forces on a TE. This is an excellent observation of changes in practice and procedural technique which has influenced the impact of the pectoralis major muscle on the breast soft-tissue pocket.…”
mentioning
confidence: 99%